Endoscopic Repair of Frontal Sinus Cerebrospinal Fluid Leaks after Firearm Injuries: Report of Two Cases - Reyes, Camilo; Solares, C. Arturo (Journal of Neurological Surgery Reports, 2015)
Objectives To describe two cases of cerebrospinal fluid (CSF) leak repair after gunshot wound to the head.Design Retrospective review of two cases.Settings A large regional tertiary care facility.Participants Two patients with gunshot wounds to the skull base.Main Outcome Measures Preoperative and postoperative physical and radiologic findings.Results Patients in this series underwent endoscopic surgery, debridement, and repair of CSF leaks after gunshot wounds to the head. To date, the patients are without CSF leak.Conclusions Endoscopic closure of anterior skull base CSF leaks in patients with gunshot wounds can be safe and effective. Treatment should be decided by the severity of neurologic deterioration throughout the emergency period and the existence or absence of associated intracranial lesions. Timing for surgery should be decided with great care and with a multidisciplinary approach.
Keywords: frontal sinus; skull base; cerebrospinal fluid leak; gunshot wounds